2005
DOI: 10.1590/s0100-46702005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric study of iron oxidation in the iron(II)/thiocyanate/acetone system and some analytical applications

Abstract: The possibility of using thiocyanate to determine iron(II) and/or iron(III) in water-acetone mixture has been re-examined as part of a systematic and comparative study involving metallic complexes of pseudohalide ligands. Some parameters that affect the complete oxidation of the ferrous cations, their subsequent complexation and the system stability have been studied to optimize the experimental conditions. Our results show the viability and potentiality of this simply methodology as an alternative analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…After this time, the absorbance of the samples was measured at the 267-nm wavelength using a 1-cm quartz cuvette. Quantification of thiocyanate ions was performed using a modification of the method described by Martins et al, which is based on the formation of a complex between iron (III) and the thiocyanate ion [38]. The reactive iron solution was prepared using 2.410 g of FeCl 3 •6H 2 O dissolved in 10% HNO 3 solution.…”
Section: Methodsmentioning
confidence: 99%
“…After this time, the absorbance of the samples was measured at the 267-nm wavelength using a 1-cm quartz cuvette. Quantification of thiocyanate ions was performed using a modification of the method described by Martins et al, which is based on the formation of a complex between iron (III) and the thiocyanate ion [38]. The reactive iron solution was prepared using 2.410 g of FeCl 3 •6H 2 O dissolved in 10% HNO 3 solution.…”
Section: Methodsmentioning
confidence: 99%
“…The data in the above table reveals that the proposed method of determination of iron is more sensitive than those reported by Malik and Rao [27], Patil and Dhuley [28], Nagabhushana et al [29], Wang et al [30], Zhang et al [31], and Martins et al [36]. The methods proposed by Katmal and Hoyakava [24], Morales and Toral [25], and Reddy et al [26] are more sensitive than the present method.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of iron can be confirmed by complexing with thiocyanate and an electronic transition at 460 nm was observed. 20 In addition, it was observed that during electrolysis, there was an increase in the deposition of the metal, probably in the form of hydroxide. In this way, electrolysis contributes to the removal of this ion from the aqueous residue and obtaining hydrogen gas, which is a clean energy source.…”
Section: Resultsmentioning
confidence: 99%
“…Iron analysis was performed on the residue formed during photoelectrolysis according to the methodology proposed in ref. 20 The concentration of dissolved iron and manganese in the collected samples was analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES) (Optima 3000 DV). Turbidity determination was performed by the nephelometric method using a turbidimeter (Hanna Instruments HI83414).…”
Section: Methodsmentioning
confidence: 99%